Kedudukan Hukum Pidana Terkait Adanya Peredaran Narkotika di Indonesia Ditinjau dari Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika - Rahmad Teguh (JURNAL RECHTENS, 2020)
This  study  is  understood  as  a  library  research  (library  research),  such  as  a  study  onsecondary data. In conclusion, the law enforcement against Narcotic Crimes according to Law on Narcotics shall give sanction of imprisonment, criminal fines, life imprisonment and other  sanctions.  The  protection  of  child  abuse  of  narcotics  from  victimology  aspects  is rehabilitated due to the child as a perpetrator and victim. The International Law on drug trafficking is the policy on preventing narcotic crimes originally provided in the United Nation's Single Convention on narcotic drugs in 1961.